Strategi Pengembangan Sumber Daya Manusia Di PUD Pasar Kota Medan - Wan Dian Safina; Khairnur Rahmah Diyah Daulay; Ayu Indira Lestari (Movere Journal, 2025)
This study conducts a literature review to examine strategies for human resource development (HRD) within the Regional Market Company (PD Pasar) of Medan City, drawing upon theoretical frameworks and previous research findings. In the context of managing traditional markets, HRD is a critical component in enhancing service efficiency, employee professionalism, and organizational competitiveness. The review identifies several strategic approaches, including continuous training, technology-driven competency development, performance management, and the cultivation of a collaborative work culture. The analysis highlights that effective HRD requires strong internal policy support, visionary leadership, and adequate resource allocation. It concludes that sustainable HRD in PD Pasar Medan should focus on strengthening individual and organizational capabilities through systematic and adaptive strategies aligned with a dynamic external environment.